An advanced structural characterization of templated meso-macroporous carbon monoliths by small- and wide-angle scattering techniques - Badaczewski, Felix M.; Loeh, Marc O.; Pfaff, Torben; Wallacher, Dirk; Clemens, Daniel; Smarsly, Bernd M. (Beilstein Journal of Nanotechnology, 2020)
This study is dedicated to link the nanoscale pore space of carbon materials, prepared by hard-templating of meso-macroporous SiO2 monoliths, to the corresponding nanoscale polyaromatic microstructure using two different carbon precursors wthat generally exhibit markedly different carbonization properties, i.e., a graphitizable pitch and a non-graphitizable resin. The micro- and mesoporosity of these monolithic carbon materials was studied by the sorption behavior of a relatively large organic molecule (p-xylene) in comparison to typical gas adsorbates (Ar). In addition, to obtain a detailed view on the nanopore space small-angle neutron scattering (SANS) combined with in situ physisorption was applied, using deuterated p-xylene (DPX) as a contrast-matching agent in the neutron scattering process. The impact of the carbon precursor on the structural order on an atomic scale in terms of size and disorder of the carbon microstructure, on the nanopore structure, and on the template process is analyzed by special evaluation approaches for SANS and wide-angle X-ray scattering (WAXS). The WAXS analysis shows that the pitch-based monolithic material exhibits a more ordered microstructure consisting of larger graphene stacks and similar graphene layer sizes compared to the monolithic resin. Another major finding is the discrepancy in the accessible micro/mesoporosity between Ar and deuterated p-xylene that found for the two different carbon precursors, pitch and resin, which can be regarded as representative carbon precursors in general. These differences essentially indicate that physisorption using probe gases such as Ar or N2 can provide misleading parameters if to be used to appraise the accessibility of the nanoscale pore space.
Keywords: adsorption; carbon materials; mesoporosity; microporosity; microstructure; pore structure; small-angle neutron scattering (SANS); wide-angle X-ray scattering (WAXS)